Estimating and predicting the distribution of the number of visits to the medical doctor - Jing Dai; Walter Zucchini; Stefan Sperlich (Philipps-University Marburg, Faculty of Business Administration and Economics, 2011)
In many countries the demand for health care services is of increasing importance. Especially in the industrialized world with a changing demographic structure social insurances and politics face real challenges. Reliable predictors of those demand functions will therefore become invaluable tools. This article proposes a prediction method for the distribution of the number of visits to the medical doctor for a determined population, given a sample that is not necessarily taken from that population. It uses the estimated conditional sample distribution, and it can be applied for forecast scenarios. The methods are illustrated along data from Sidney. The introduced methodology can be applied as well to any other prediction problem of discrete distributions in real, future or any fictitious population. It is therefore also an excellent tool for future predictions, scenarios and policy evaluation.
Keywords: I12; C51; C53; H75; 330; predicting health care demand; visits to the doctor; health economics; model selection; Gesundheitswesen; Nachfrage; Konsumentenverhalten; Prognoseverfahren; Statistisches Auswahlverfahren; Schätztheorie; Theorie; Australien